Cytomegalovirus-specific T-cell responses and viral replication in kidney transplant recipients - Sester Urban; Steiger Juerg; Schaub Stefan; Dumoulin Alexis; Jäger Clemens; Binggeli Simone; Binet Isabelle; Egli Adrian; Sester Martina; Hirsch Hans H (Journal of Translational Medicine, 2008)
Abstract Background Cytomegalovirus (CMV) seronegative recipients (R-) of kidney transplants (KT) from seropositive donors (D+) are at higher risk for CMV replication and ganciclovir(GCV)-resistance than CMV R(+). We hypothesized that low CMV-specific T-cell responses are associated with increased risk of CMV replication in R(+)-patients with D(+) or D(-) donors. Methods We prospectively evaluated 73 consecutive KT-patients [48 R(+), 25 D(+)R(-)] undergoing routine testing for CMV replication as part of a preemptive strategy. We compared CMV-specific interferon-γ (IFN-γ) responses of CD4+CD3+ lymphocytes in peripheral blood mononuclear cells (PBMC) using three different antigen preparation (CMV-lysate, pp72- and pp65-overlapping peptide pools) using intracellular cytokine staining and flow cytometry. Results Median CD4+ and CD8+T-cell responses to CMV-lysate, pp72- and pp65-overlapping peptide pools were lower in D(+)R(-) than in R(+)patients or in non-immunosuppressed donors. Comparing subpopulations we found that CMV-lysate favored CD4+- over CD8+-responses, whereas the reverse was observed for pp72, while pp65-CD4+- and -CD8+-responses were similar. Concurrent CMV replication in R(+)-patients was associated with significantly lower T-cell responses (pp65 median CD4+ 0.00% vs. 0.03%, p = 0.001; CD8+ 0.01% vs. 0.03%; p = 0.033). Receiver operated curve analysis associated CMV-pp65 CD4+ responses of > 0.03% in R(+)-patients with absence of concurrent (p = 0.003) and future CMV replication in the following 8 weeks (p = 0.036). GCV-resistant CMV replication occurred in 3 R(+)-patients (6.3%) with pp65- CD4+ frequencies < 0.03% (p = 0.041). Conclusion The data suggest that pp65-specific CD4+ T-cells might be useful to identify R(+)-patients at increased risk of CMV replication. Provided further corroborating evidence, CMV-pp65 CD4+ responses above 0.03% in PBMCs of KT patients under stable immunosuppression are associated with lower risk of concurrent and future CMV replication during the following 8 weeks.